PERANAN UMPASA/UMPAMA DALAM BUDAYA BATAK TOBA TERHADAP KATEKESE DI PAROKI SANTO PAULUS ONAN RUNGGU - Lumban Tobing, Ona Sastri (IN VERITATE LUX, 2021)
The enhancement of religious education within society is influenced by various factors, including culture, which plays a significant role in shaping personalities and knowledge of the Christian faith. This study aims to examine the extent of the influence of "umpasa/umpama" in Batak Toba culture on religious education in the Parish of Saint Paulus Onan Runggu. The research method employed is descriptive with a quantitative approach. The study population comprises adult parishioners of Saint Paulus Onan Runggu, with a sample size of 40 individuals. The validity of the research instrument was tested using the Product Moment correlation formula, and the instrument's reliability was assessed using the Spearman Brown formula. The data analysis showed that the calculated chi-square (x²) was greater than the table chi-square (x²), indicating that the hypothesis could be accepted. The critical value of the Product Moment correlation at a 95% confidence level, with a correlation coefficient (r) of 0.312 and a sample size (N) of 40, was computed. The hypothesis testing result for the role of "umpasa/umpama" in Batak Toba culture as variable X on religious education in the Parish of Saint Paulus Onan Runggu as variable Y yielded a calculated t-value of 0.708, which was compared to the table value of 0.312. If the calculated t-value exceeds the table value, the hypothesis is accepted; otherwise, it is rejected. Therefore, the hypothesis is accepted, indicating that "umpasa/umpama" in Batak Toba culture significantly influences religious education in the Parish of Saint Paulus Onan Runggu.